(untitled) (Revista de Investigaciones Universidad del Quindío, 2015)
In 2012 in Colombia, there was panic among women with mammary prosthesis (PIP) because of a news report that explained that they contained industrial silicon, a product that could cause cancer in the women that used them. Objective. To determine the presence of atypical proliferative changes in the biopsies of the mammary glands of women recipients of the prosthesis. Methodology. A descriptive study that took a cross-section of the population affected was conducted on the histopathological changes found in bilateral, tru-cut biopsies of the mammary gland with the previous informed consent of fi fty women patients that were recipients of the mammary prosthesis. All had requested that their prosthesis be changed at the Clinic of Plastic Surgery in the city of Armenia, Quindio, Colombia during the period from March to December 2012. Their information was entered into an Excel data base and a statistical analysis was done by Statgraphics Centurion 1.15 Results. Biopsies were conducted of both mammary glands of fi fty women prosthesis users. The tissue was representative in both breasts in 29 of the women (58%), in 3 users (6%) fi broadipose tissue was found in both breasts, and in 9 (18%) patients only tissue from the right breast was studied. In twelve users (24%), only the tissue of the left breast was studied because the contralateral biopsie showed adipose tissue. There were not any atypical proliferative changes in any of the women. In 6 users (12%), fi brocystic changes were found. In the remaining 41 users (82%), the mammary tissue was normal.